[PP.22.07] RAPID TREATMENT OF NEWLY-DIAGNOSED MODERATE-SEVERE HYPERTENSION IS SAFE AND EFFECTIVE. (September 2017) - Jordan, A.; Anning, C.; Ball, C.; Wilkes, L.; Pamphilon, N.; Clark, C.; Shore, A.; Sharp, A.
Abstract : Objective: There is growing evidence to suggest that timing of BP control in subjects with hypertension influences future risk of cardiovascular events. The safety and feasibility of delivering an accelerated treatment programme to rapidly control newly-diagnosed hypertension is unknown. We sought to determine whether patients with newly-diagnosed moderate-severe hypertension could be effectively and safely treated to target by 18 weeks. Design and method: Patients aged 18–79 years with never-treated grade II-III hypertension were recruited following a usual care office systolic BP of >170 mmHg and subsequent ambulatory systolic BP of >150 mmHg. Once recruited, participants underwent a nurse-led protocol following consensus guidelines on BP treatment, delivered over an accelerated timeframe. Medication was intensified in a stepwise fashion following the protocol in those not at target BP during follow-up. Those demonstrated to be resistant to treatment underwent adherence testing with directly observed therapy and robust exclusion of secondary causes. The primary outcome was the proportion of participants achieving target office BP (<140/90 mmHg) at week 18 versus usual care. Results: 34 participants (41% female) with a median age of 64.5 years were enrolled and completed the 18-week protocol with no dropouts. A further 20 completed participants are expected by the time of presentation. When repeated by the study team at screening, median entry office BP was 176/101mmHg and daytime average ambulatory BP was 162/92mmHg. After 18 weeks, these reduced to medians of 136/79mmHg and 134/75mmHg respectively. 65% participants were at office BP target at 18 weeks. This was a significantly higher proportion than usual care in the referring area (44.4%) (p = 0.016). Creatinine increased >30% above baseline after candesartan initiation in 2 participants, requiring its discontinuation. In both cases, creatinine returned to normal within 2 weeks. 4 participants discontinued or reduced their dose of thiazide diuretic due to lightheadedness and 2 did not tolerate amlodipine. There were no episodes of syncope and no instances of discontinuation or deviation from the pre-defined protocol. Conclusions: Moderate-severe hypertension can be treated effectively and safely in 18 weeks, thereby potentially minimising subsequent cardiovascular events.